Effects of African BaP emission from wildfire biomass burning on regional and global environment and human health. (April 2022) - Wu, Min; Luo, Jinmu; Huang, Tao; Lian, Lulu; Chen, Tianlei; Song, Shijie; Wang, Zhanxiang; Ma, Shuxin; Xie, Chaoran; Zhao, Yuan; Mao, Xiaoxuan; Gao, Hong; et al.
Graphical abstract: Highlights: BaP emissions from biomass burning are updated to assess the significance of nature sources. BaP released from African wildfires is making increasing contribution to global BaP emission. Remarkable high BaP concentrations in Africa contribute its contamination to other continents. Residents in many sub-Saharan countries suffer from inhalation exposure risk to BaP emitted from wildfires. Abstract: The vegetation burning caused by wildfires can release significant quantities of aerosols and toxic chemicals into the atmosphere and result in health risk. Among these emitted pollutants, Benzo(a)pyrene (BaP), the most toxic congener of 16 parent PAHs (polycyclic aromatic hydrocarbons), has received widespread concerns because of its carcinogenicity to human health. Efforts have been made to investigate the environmental and health consequences of wildfire-induced BaP emissions in Africa. Still, uncertainties remain due to knowledge and data gaps in wildfire incidences and biomass burning emissions. Based on a newly-developed BaP emission inventory, the present study assesses quantitatively the BaP environment cycling in Africa and its effects on other continents from 2001 to 2014. The new inventory reveals the increasing contribution of BaP emission from African wildfires to the global total primarily from anthropogenic sources, accounting for 48% since the 2000 s. We identify significantly higher BaP emissions and concentrations across sub-Saharan Africa, where the annual averaged BaP concentrations were as high as 5–8 ng/m 3 . The modeled BaP concentrations were implemented to estimate the lifetime cancer risk (LCR) from the inhalation exposure to BaP concentrations. The results reveal that the LCR values in many African countries exceeded the acceptable risk level at 1 × 10 −6, some of which suffer from very high exposure risk with the LCR>1 × 10 −4 . We show that the African BaP emission from wildfires contributed, to some extent, BaP contamination to Europe as well as other regions, depending on source proximity and atmospheric pathways under favorable atmospheric circulation patterns.